A Bifunctional Fully Integrated Wearable Tracker for Epidermal Sweat and Wound Exudate Multiple Biomarkers Monitoring. Issue 46 (30th September 2022) - Pei, Xinyi; Sun, Mimi; Wang, Jingjuan; Bai, Jing; Bo, Xiangjie; Zhou, Ming
Abstract: Fully integrated wearable electronics that combine the extraordinary feature of incessant and on‐body operation with the distinctive external equipment‐free trait are the ultimate goal of modern wearables. Epidermal sweat and wound exudate, as two noninvasively accessible biofluids on/surrounding the skin, reflect underlying health conditions. However, the design of universal wearable sensors with the bifunctional capability to monitor both epidermal secretions is still a challenge. Here, a single bifunctional fully integrated wearable tracker for wirelessly, simultaneously, and dynamically in situ measuring multiple epidermal sweat or wound exudate biomarkers is propos. Considering the electrolytes (e.g., Na +, K +, and H + ) and metabolites (e.g., uric acid (UA)) levels in sweat or wound exudate may correlate with health or wound conditions, the dynamic and skin‐on tracking of the biomarkers of Na +, K +, pH, and UA levels in sweat under subjects' exercise and in wound exudate during subjects' wound healing are performed through the seamless integration of microfluidic, sensing, and electronic modules. Its applicability is evaluated for noninvasive hyperuricemia management in hyperuricemia/healthy subjects through a purine‐rich intake test and for wound management in subjects' infected wounds through a control medical treatment. Abstract : A bifunctional fully integrated wearable epidermal sweat and wound exudate tracker is engineered for wireless, dynamic, and simultaneous in situ tracking of epidermal sweat or wound exudate electrolytes (Na +, K +, and H + as model analytes) and metabolites (uric acid as model analyte) appearing on/surrounding the skin for potential noninvasive hyperuricemia or wound management.